Association between trunk core muscle thickness and functional ability in subacute hemiplegic stroke patients: an exploratory cross-sectional study. Issue 3 (3rd April 2022) - Suh, Jee Hyun; Lee, Eun Chae; Kim, Joo Sup; Yoon, Seo Yeon
ABSTRACT: Back ground: Balance impairment could occur due to weakness of the core muscles in stroke patients. Objective: To investigate the association between functional ability, including trunk balance and core muscle thickness using ultrasonography in subacute hemiplegic stroke patients. Methods: The muscle thickness of the anterior and posterior trunk muscles was measured using ultrasonography. For the evaluation of trunk balance, trunk impairment scale and Berg balance scale (BBS) were used. The functional ambulatory scale (FAS), timed up-and-go test, 10 m gait velocity, functional reach (FR), and functional independence measure were also assessed for functional ability. Results: Overall, 41 patients with subacute hemiplegic stroke were included. Partial correlation analysis showed that posterior trunk muscle thickness was significantly correlated with BBS, FAS, and FR. As for the paralytic side, the posterior trunk muscle thickness of both paretic and nonparetic sides presented a significant relationship with BBS, FAS, and FR. The quadratus lumborum (QL) thickness of both sides showed a significant relationship with BBS, FAS, and FR. Conclusions: The thickness of the posterior trunk muscles, especially the QL, on both the paretic and nonparetic sides, was significantly related with the functional ability after stroke. The exercise program of core posterior trunk muscles closely related with functional ability would be helpful to improve trunk balance and ambulatory function in subacute stroke patients.